Radiation Protection in an Interventional Laboratory: A Comparative Study of Australian and Saudi Arabian Hospitals - Alahmari, M.; Sun, Zhonghua; Bartlett, A. (Oxford University Press, 2016)
This study aimed to investigate whether the use of protection devices and attitudes of interventional professionals (including radiologists, cardiologists, vascular surgeons, medical imaging technicians and nurses) towards radiation protection will differ between Saudi Arabian and Australian hospitals. Hard copies of an anonymous survey were distributed to 10 and 6 clinical departments in the Eastern province of Saudi Arabia and metropolitan hospitals in Western Australia, respectively. The overall response rate was 43 % comprising 110 Australian participants and 63 % comprising 147 Saudi participants. Analysis showed that Australian respondents differed significantly from Saudi respondents with respect to their usages of leaded glasses (p < 0.001), ceiling-suspended lead screen (p < 0.001) and lead drape suspended from the table (p < 0.001). This study indicates that the trained interventional professionals in Australia tend to adhere to benefit from having an array of tools for personal radiation protection than the corresponding group in Saudi Arabia